(untitled) (Fiep Bulletin - online, 2017)
The great improvement in performance is based on increasing physical abilities, being observed from year to year, themore the adolescent improves strength, stamina, reaction time, movement speed, coordination and so on, we can expect toobserve performance levels every time best. Physical fitness is described as the ability to perform physical activities with energyand vigor without excess of fatigue and also as the demonstration of qualities and physical abilities that lead to the lower risk ofdevelopment of functional diseases and incapacities. Speed is a hybrid capacity conditioned by all others. It is classified incyclical and acyclic speed with three phases for both manifestations: acceleration, maximum speed and speed resistance, being the fundamental acceleration in sports activities such as the 60m, 100m, 200m race, and in the cooperative and oppositiongames ) When associated with decision-making capacity. The methodology was a Displacement Speed Test battery (20-meterrun). The data presented here show that the 38 subjects evaluated before and after a periodization through the development ofsports modalities, obtained similar results in the pre and post test, and this difference was not significant with p = 0.711. Accordingto the mean and standard deviation we can consider it satisfactory, but it takes us a reflection regarding the intensity and durationof the activities proposed in the periodization. At the end of this research it was concluded that diversified sportsmen and womenmaintained the speed pattern, but the difference between the beginning and the end of periodization was not significant. We canconsider as important determinants of velocity the type of activity proposed, the training time and the specificities of eachmodality, being able to select and adapt activities appropriate to the objectives of each one.